Perceptions of the Use of the Diode Laser in Dental Surgery: A Qualitative Study - Kamila Gomes Soares; Tallyta Yohana Andrade de Carvalho; Alice Machado Carvalho Santos; Lívio Barros Silveira; Lidiane Cristina Machado Costa; Maria Luiza da Matta Felisberto Fernandes; Alexandre Moreira Fernandes (Association of Support to Oral Health Research (APESB), 2022)
Objective: To discover the perceptions of pediatric patients, their parents and undergraduate Dentistry students of the use of the diode laser in frenectomy surgeries. Material and Methods: A qualitative study was conducted through semi-structured interviews, recorded and transcribed with subsequent content analysis. Twelve healthy children (5-8 years old) who needed a frenectomy were selected and invited, together with their parents, to undergo laser diode surgery. In addition, 28 undergraduate  dentistry students were invited to attend the procedures. One week after performing the surgical procedures, the children (Group 1), their parents (Group 2) and the students who attended the procedures (Group 3) were individually interviewed for the thematic analysis. Results: The analysis of the conversations identified three emerging contents: positive thoughts on the use of diode laser; frustrations from the use of diode laser; and aspects related to professional training. Conclusion: The results pointed to the acceptance of surgical laser use in pediatric dentistry; however, the feelings of frustration indicate that its use requires guidance from the child and his/her parents, in addition to careful handling and specific training.